Expansão de células mesenquimais estromais em frasco spinner e avaliação de aditivos para diminuir a aglomeração de microcarregadores - Mendonça, Marlei Leandro de (Universidade Federal de São Carlos, 2013)
The increasing interest in the employment of multipotent mesenchymal stromal cells (MSCs) to applications in tissue engineering and cell therapy is mainly attributed to their plasticity and regenerative capacity. The MSCs represent a revolution in the treatment of countless diseases and in the understanding of tissue repair mechanisms. Due to their low availability in the tissues (0.00001% to 0.0002%) as well as to the need of high doses for therapeutic applications (approximately 2 x 106 cells/kg patient), and to the inefficiency of traditional in vitro cultures (in monolayer) to meet the existing high demand to these applications, development of new technologies of ex vivo expansion on a large scale became indispensable. The use of spinner flasks-like bioreactors with microcarriers in suspension is an effective alternative system for this expansion. However, bibliographic report of cultures with this system have indicated the formation of large clusters of microcarriers with cells as a possible obstacle to obtain a greater cellular productivity. These clusters hamper the diffusion of nutrients, gases (especially oxigen), and reagents of indirect cellular quantification within them; and they harm the cell recovery at the end of culture. Alginate microspheres have become interesting to reduce the frequency of collisions between microcarriers, due to the fact that the microspheres do not adhere to cells nor to microcarries and can prevent the union of same. The dextran sulfate has been described in the literature as an inhibitor of cell-to-cell contact as well as of the encounter between microcarriers in culture, therefore, it too has become a promising option to avoid the formation of clusters of microcarriers. Thus, the aim of this work was to develop a methodology for the culture of MSCs in spinner flasks with microcarriers Cultispher-S for application in cell therapy and evaluate the influence of alginate microspheres and dextran sulfate on this culture. For this, the lineage hMSCTERT and 3 g/L Cultispher-S were held in 100 mL spinner containing α-MEM culture medium (supplemented with 15% of bovine fetal serum, glucose and glutamine) at 37ºC, with pH control. The results showed that the addition of dextran sulfate (at 0.5% and 1%) and of 100% of alginate microspheres (in relation to the number of Cultspher-S particles) to the culture caused considerable cell death; and the control (without additives) as well as the addition of 50% of alginate microspheres promoted cell growth. The formation of clusters was observed in cultures; however, it was delayed with the addition of 50% of alginate microspheres. This occurrence allowed a cellular expansion factor of 50.4 times (with dilution factor correction) and of 13.1 times (without correction). The recovered cells after expansion kept their immunophenotypic characteristics.
Keywords: Biotecnologia; Células-tronco; Biorreatores; Microcarregadores - aglomerados; Microesferas de alginato; Sulfato de dextrana; Stem cell; Bioreactor; Microcarrier; Clusters; Dextran sulfate; Alginate microspheres; OUTROS